1999
DOI: 10.1152/physrev.1999.79.4.1127
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Transport of Cations: Channels, Exchangers, and Permeability Transition

Abstract: This review provides a selective history of how studies of mitochondrial cation transport (K+, Na+, Ca2+) developed in relation to the major themes of research in bioenergetics. It then covers in some detail specific transport pathways for these cations, and it introduces and discusses open problems about their nature and physiological function, particularly in relation to volume regulation and Ca2+ homeostasis. The review should provide the basic elements needed to understand both earlier mitochondrial litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
1,266
1
26

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,423 publications
(1,319 citation statements)
references
References 365 publications
(370 reference statements)
26
1,266
1
26
Order By: Relevance
“…VDAC, a major mitochondrial outer membrane transporter, plays an important role in apoptosis by participating in the release of intermembrane space proteins including cytochrome c. 3,4,6,[8][9][10][33][34][35] Investigating the role of VDAC in cellular processes is, however, limited by a lack of tools such Figure 3 RuR inhibits channel activity of native but not E72Q-mutated mVDAC1. Purified native or E72Q-mVDAC1 was reconstituted into a PLB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VDAC, a major mitochondrial outer membrane transporter, plays an important role in apoptosis by participating in the release of intermembrane space proteins including cytochrome c. 3,4,6,[8][9][10][33][34][35] Investigating the role of VDAC in cellular processes is, however, limited by a lack of tools such Figure 3 RuR inhibits channel activity of native but not E72Q-mutated mVDAC1. Purified native or E72Q-mVDAC1 was reconstituted into a PLB.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4]6 The PT is thought to comprise the adenine nucleotide translocase (ANT), cyclophilin D and the voltagedependent anion channel (VDAC). [2][3][4][6][7][8][9][10] The Ca 2 þ binding component of the permeability transition pore (PTP) has not yet been identified, although Ca 2 þ modulation of the ANT has been suggested. 11 On the other hand, several studies have shown that VDAC is permeable to Ca 2 þ and possesses Ca 2 þ binding site(s), suggesting the involvement of these sites in the regulation of VDAC activity, as well as of PTP opening.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of selective permeability was initially thought to be caused by defects in the lipid moiety of the membrane, consequent to activation of phospholipase A 2 by elevated Ca 2ϩ levels (Pfeiffer et al, 1979;Beatrice et al, 1980). The alternative hypothesis, that MPT results from the opening of a pore or megachannel, referred to as the permeability transition pore (PTP) transversing both mitochondrial membranes (Hunter and Haworth, 1979;Zoratti and Szabo, 1995;Bernardi, 1999), has been extensively investigated and is currently widely accepted.…”
mentioning
confidence: 99%
“…17 The proximity between ER and mitochondria reflects a close functional communication between the two organelles, in particular in the context of Ca 2 þ signalling. The activation of the low-affinity mitochondrial Ca 2 þ uniporter, responsible for mitochondrial Ca 2 þ uptake, 18 requires that the mitochondria are exposed to high Ca 2 þ microdomains originated at the mouth of inositol trisphosphate receptors at the surface of the ER. 19 Mitochondrial Ca 2 þ uptake is crucial to shape cytosolic Ca 2 þ oscillations 20 and in turn to modulate mitochondrial function, including activation of mitochondrial metabolism 21 and control of the permeability transition (PT) pore, a Ca 2 þ and voltage-dependent channel of the inner mitochondrial membrane that participates in certain models of apoptosis.…”
mentioning
confidence: 99%
“…19 Mitochondrial Ca 2 þ uptake is crucial to shape cytosolic Ca 2 þ oscillations 20 and in turn to modulate mitochondrial function, including activation of mitochondrial metabolism 21 and control of the permeability transition (PT) pore, a Ca 2 þ and voltage-dependent channel of the inner mitochondrial membrane that participates in certain models of apoptosis. 18 Recent works show that these structural features can play a role in the control of apoptosis. On one side, Ca 2 þ signalling between ER and mitochondria is crucial in the regulation of certain apoptotic pathways.…”
mentioning
confidence: 99%